Sustainable Development Goals: Strategy for Increasing Human Resources Towards the Independence of MSMEs - Jonathan Giovanni; Pratiwi Subianto; Mirna Sugiarti; Hezty Wahyu Utami (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Objective - This research was conducted to design a strategy model for increasing human resources towards the independence of MSMEs in Palangka Raya City in realizing Sustainable Development Goals. Design/Methodology/Approach - The method that will be used in this research is the soft system methodology (SSM). This method is almost the same as other systems approaches, where the essence of SSM is to provide a comparison between the real situation in the implementation of MSMEs and a model designed to represent the world itself. Research findings - based analysis, it is known that relevant human resource development in improving the development of MSMEs in Palangka Raya City includes business protection, business policies, business operational systems, business administration, ability to innovate, ability to identify opportunities, which can be done with openness and participatory and able to look for opportunities to anticipate change. Implications –The government needs to support the provision of infrastructure and learning instruments in the form of instructions and regulations, and the involvement of industry and the private sector needs to be encouraged to contribute through the provision of capital and business assistance.